Ответы и объяснения

2013-02-22T18:10:24+00:00

1)An=9-3n     

найдем a1=9-3=6, a8=9-3*8=9-24=-15

S8=(6-15)*4=-36         Sn=(a1+an)/2*n  

 

2)a1=3, S7=0, d-?  Sn=(2a1+(n-1)*d)/2*n

 

подставляем в формулу, получаем  0=(2*3+(7-1)d)*3,5

                                                                   0=(6+6d)*3,5

                                                                   0=6+6d отсюда d=-1

d=-1

3)c1=-4, S9=72аналогично пункту 2

 

72=(2*(-4)+8d)*4,5

72=(-8+8d)*4,5

16=-8+8d

24=8d

d=3

ответ 3

 

  • Yena
  • главный мозг
2013-02-22T18:25:30+00:00

.........................................................................................